A Study on China’s Tobacco Taxation and Its Influencing Factor on Economic Growth - Zhao, Shuang (Frontiers in Psychology, 2022)
Tobacco is a significant product providing considerable economic benefits to countries worldwide, while its increased consumption causes health and socio-economic losses for smokers and non-smokers. This paper constructs a decomposition system of tobacco taxation: the population aging factor is included in the influencing factors of personal tax, and personal tax revenue is regarded as the product of tax structure, macro tax burden, regional economy, reciprocal aging, and the elderly population. This article conducts an empirical study on the relationship between taxation and economic growth. The estimated coefficients of business tax and corporate income tax are significant at the significance level of 0.1, with a consumption tax and time-variable coefficients reporting a 0.02 level of significance. The T statistic value and the explanatory degree of the variables involved in the model to the explained variables are also very high, reaching more than 95%. We find that increasing the macro tax burden negatively impacts economic growth. Therefore, the study suggests that for fostering the industry's economic growth, the country needs to ensure the optimal macro tax burden of 17.5%, with different types of taxes influencing economic growth. Personal tax reform should pay attention to the phenomenon of aging, adjust the tax structure to increase personal tax income, provide policy support and guarantee for the elderly labor force, and encourage the re-employment of silver-haired people to alleviate the adverse impact of aging on taxation.